Kompas Yang Salah Arah: Kritik Teologis Terhadap Fenomena Stoisisme Populer Di Generasi Dan Urgensi Kembali Kepada Firman - Hengki Irawan Setiabudi (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This study examines the phenomenon of Generation Z's attraction to popular Stoicism, particularly through the book Filosofi Teras, as a perceived answer to anxiety and life pressures in the digital era. Using a qualitative descriptive-comparative method based on library research, this study finds that what Generation Z actually consumes is not classical Stoicism but pseudo-stoicism, a shallow form that risks deepening emotional suppression and social isolation. A structural comparison across six fundamental needs shows that popular Stoicism consistently centers on the self, whereas Scripture locates self-mastery, hope, and transformation in the work of the Holy Spirit and Christian community. Departing from prior scholarship that adopts an accommodating stance toward Stoicism, this study takes a corrective position, arguing that Generation Z's attraction to this teaching reflects a symptom of spiritual emptiness rather than its solution, a compass pointing in the wrong direction. The study recommends church discipleship that presents Scripture in ways directly responsive to the concrete struggles of the younger generation.